URGENSI PENDIDIKAN TOLERANSI DALAM MASYARAKAT MULTIKULTURAL (Studi Analisis QS. Al Baqarah ayat 256 dan QS. Al Hujurat ayat 13) - Zaidul Arzaq, Robbi Shofri; Nur Salim, Muhammad; Said, Ali (EL-Islam, 2020)
This article discusses the importance of the education oftolerance in the life of multicultural society from the perspective ofthe al Quran. The purpose of this article is 1) To describe theeducation of tolerance contained in the al Quran surah al Baqarah256, 2) To describe the multicultural concept of society contained inthe al Quran surah al Hujurat 13, and 3)To describe the urgency ofthe education of tolerance in the multicultural society contained inthe al Quran surah al Baqarah 256 and the al Quran surah al Hujurat13. The research methodology used in this article is to use aqualitative approach, while the type of research uses the type oflibrary research. The results of research describe that 1) Islam doesn’tforce people to embrace Islam, for the path of truth and heresy isalready in sight. So, common sense would choose the right way forhim to walk. 2) Man of all kinds is already God’s power. But, withsuch differences, it is God’s will for mankind to know and benefitone another. Because a person’s glory on the side of God lies in hisobedience level. 3) The growing tolerance of a multiculti society isessential to a harmonious, peaceful, and harmonious life.